Pemberdayaan Masyarakat Desa Jia Kecamatan Sape Kabupaten Bima - Wawan Mulyawan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
The implementation of infrastructure development in the form of concrete alley rebates, the Jia Village Government and the community carry it out collectively and collegially, in its implementation the participation of the Jia Village community is quite extraordinary because all elements of the community participate with the aim of empowering the community through various development programs so that it is sustainable between the community and the government so as to create a Jia Village community that is aware of the importance of community empowerment-based development.da several strategies that must be taken in increasing community participation in development activities. Firstly, there needs to be a perception from all components of society from various stratifications of society, starting from the general public, social organizations, OKP, LPMD, PKK, and other elements about the importance of participation; secondly, optimizing the participation of community leaders/leaders to foster and motivate community members in increasing understanding and understanding of the importance of participation; thirdly, increasing the role of social organizations as a mass mobilizer in order to create community participation.